An Analysis of Water Infiltration in Furrow Irrigation Channels with Plants in Various Types of Soil in the Special Region of Yogyakarta Using Dual Reciprocity Boundary Element Method - Irene, Yanne; Manaqib, Muhammad; Ramadhanty, Vina Wulandari; Ria Affriani, Asri (JTAM (Jurnal Teori dan Aplikasi Matematika), 2024)
The analysis of water infiltration channels requires significant time and cost when conducted through laboratory experiments. Alternatively, mathematical modeling followed by numerical method can be employed. The mathematical model of water infiltration in furrow irrigation channels takes the form of a boundary value problem, with the Helmholtz equation serving as the governing equation. The Dual Reciprocity Boundary Element Method (DRBEM) is a numerical method derived from the Boundary Element Method (BEM), utilized for solving partial differential equations encountered in mathematical physics and engineering. This research employs DRBEM to analyze infiltration in trapezoidal irrigation channels with root-water uptake across various homogeneous soil types prevalent in agricultural lands in each District/City of the Yogyakarta Special Region Province. The results demonstrate that DRBEM provides numerical solutions for suction potential, water content, and root water absorption for each soil type. It was found that sandy soil exhibits high water content but has a low rate of root water absorption. On the other hand, clayey soil has low water content but a higher rate of root water uptake. These findings indicate that sandy soil, such as those found in Sleman District and Yogyakarta city, are less efficient in water usage when employing the furrow irrigation system, whereas clayey soil, as found in Gunung Kidul regency, is more effective.